An Anxiety Analysis of Student in Learning English at the 10th Grade of SMA 7 Kota Tangerang - Septiana, Siti Zaenafsih; Agustina, Hiqma Nur (Foremost Journal, 2020)
Abstract This research was carried out to investigate foreign language anxiety of EFL senior high school students at the 10th grade of SMAN 7 Kota Tangerang. Specifically, it aimed to identify what factors that may contribute to anxiety in English learning environment based on the students' perspectives. The method was used in this study was descriptive qualitative method. Fifteen anxious students were selected as the participants. The data were gathered through structured interviews and classroom observations. The result of the study showed that speaking in front of the class is the dominant factor of students' anxiety, then being laughed at by others, incomprehensible input, students' beliefs about language learning, teacher personality and attitude, and lack of preparation were the six factors that may contribute to the students' anxiety in learning English.